Learning from lessons learned, How to preserve knowledge and improve relations to decrease additional costs and quality defects in new housing projects - Hellqvist, Mikaela Landin; Wetterberg, Anna (My University, 2016)
The construction of new housing depends on a wide range of different actors. Well-functioning relations are vital for project success despite this, challenges concerning relations are often overlooked for the sake of financial results. Price is considered the most important factor when tendering subcontractors, risking compromising other important aspects. Yet another factor impacting a project’s outcome is errors. As all profit making organisations strive to increase profitability, these are essential to rectify, analyse and learn from. Previous research indicates that quality defects primarily occur due to organisational issues. It is challenging for construction companies to systematically monitor quality defects and capture lessons learned. The long-term perspective is often sacrificed for the sake of short-term success, impeding learning within and between organisations. Through qualitative research, the authors have conducted a literature review of project organisations, common disturbances in projects, knowledge management, and main contractor-subcontractor relations in the field of construction management. Furthermore, a case study was conducted at a large construction company in Sweden. The study aimed to investigate how new housing projects in the construction industry can decrease additional costs and quality defects, through improved relation, as well as by implementing knowledge management systems. The study indicated that the Company has to create a culture for prioritising knowledge transfer and capturing lessons learned. The challenge to monitor and analyse quality defects in the construction industry is evident, as neither main contractors nor subcontractors learn from previous mistakes to the extent possible. Implementing learning networks and conducting post project reviews (PPR: s) are recommended ways to foster knowledge exchange, and improving organisational learning. The study indicates a tendency for undervaluing design in early phases, resulting in defects and ambiguity in division of responsibilities. By adopting the long-term perspective, construction companies can increase their ability to create stable organisations and projects with higher predictability, hence increase the ability to predict which projects will be profitable and less troublesome in the future.
Keywords: Samhällsbyggnadsteknik; Civil Engineering